Beyond the rainbow: Attitudes of Brazilian consumers regarding homoaffective advertisements - Estela Maria Hoffmann; Maria José Barbosa de Souza; Melanie Morrison; Todd Morrison (BBR: Brazilian Business Review)
Although there is societal pressure to accept diversity, negative attitudes towards minority groups such as gay men and lesbian women, especially in Brazil, remain widespread. The objective of this study was to examine whether gender, religiosity, and homonegative attitudes are associated with evaluations of homoaffective advertisements, brand, and purchase intentions. A survey with 456 university students from southern Brazil was carried out. The results demonstrate that women have more positive attitudes towards homoaffective advertisements, brands, and purchase intention. Religiosity also interferes with the attitude towards the ads and the attitude towards the brand. When analyzing religiosity and homonegativity by gender in attitudes towards the advertisement, brand, and purchase intention, it is observed that, for men, religion does not interfere in the attitude towards the brand and in the purchase intention. Limitations of the current study, and directions for future research are outlined.